If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 3n + -8n = -7 Combine like terms: 3n + -8n = -5n 3 + -5n = -7 Solving 3 + -5n = -7 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -5n = -7 + -3 Combine like terms: 3 + -3 = 0 0 + -5n = -7 + -3 -5n = -7 + -3 Combine like terms: -7 + -3 = -10 -5n = -10 Divide each side by '-5'. n = 2 Simplifying n = 2
| -9=5q/2-1/4(-6q+4) | | 163=4x+3(1-8k) | | 30x=6x-54 | | 5/3+17/6 | | 7a-9=-19+6a | | 110+.40x=30+.80x | | 8v+v=9 | | 4y+2y=48 | | 45y^3z^10/5y^3z | | f(x)=7x^2-4x | | k-1/3(1-9k)=2/3 | | y=2x-1forx | | 22-8m=-8m-11m | | 9+6m=45 | | -4-6n=5-9n | | (m^5n)^-2/m^-2n^3 | | x+3+3x-(6)=180 | | 1.2-0.3m=1.8 | | z(z^2+1)=5+z^3 | | 1=k+8/15 | | 6/7*9/16 | | -7k-k=-10k | | -116=-7x+2(-7x+5) | | 4.8/3 | | -7k-k=10k | | x(6x-6)=(6+8)(x-7) | | 15+3x+1=7x+1 | | 6(-2)-3(-5)/4-2 | | 3x^3+2x^2y+3xy^2+2y^3= | | 2a-5b/6a-4a+5b/4a+2 | | 3x^3+2x^2v+3xy^2+2y^3= | | 3x-4=6x+5 |